2016
DOI: 10.1097/igc.0000000000000673
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Treatment of Metastatic Ovarian Tumors From Extragenital Primary Sites

Abstract: The most common primary sites for ovarian metastasis are gastrointestinal tract. Metastasectomy may have beneficial effects on survival, especially if the residual disease is less than 5 mm. Prospective studies warranted to evaluate the value of metastasectomy in patients with ovarian metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…Moreover, the prognosis of STOs that originate from a previously diagnosed malignancy is considerably better than in tumors presenting primarily as ovarian metastases. Several prognostic factors have been identified: pre-operative carbohydrate antigen 125 (CA 125) level in serum, age at diagnosis of STOs, pre-operative STO size [ 21 ], primary tumor origin [ 9 ], presence of peritoneal dissemination [ 20 ], extent of cytoreductive surgery [ 16 , 22 ], and unilaterality versus bilaterality [ 21 ]. Furthermore, mutations of the SMAD family member 4 ( SMAD4 ) and lysine methyltransferase 2D ( KMT2D ) genes are associated with reduced OS in ovarian metastases from CRC [ 23 ], indicating that somatic mutation profiling may provide additional prognostic information.…”
Section: Prognosismentioning
confidence: 99%
“…Moreover, the prognosis of STOs that originate from a previously diagnosed malignancy is considerably better than in tumors presenting primarily as ovarian metastases. Several prognostic factors have been identified: pre-operative carbohydrate antigen 125 (CA 125) level in serum, age at diagnosis of STOs, pre-operative STO size [ 21 ], primary tumor origin [ 9 ], presence of peritoneal dissemination [ 20 ], extent of cytoreductive surgery [ 16 , 22 ], and unilaterality versus bilaterality [ 21 ]. Furthermore, mutations of the SMAD family member 4 ( SMAD4 ) and lysine methyltransferase 2D ( KMT2D ) genes are associated with reduced OS in ovarian metastases from CRC [ 23 ], indicating that somatic mutation profiling may provide additional prognostic information.…”
Section: Prognosismentioning
confidence: 99%
“…Research by several authors indicates that the average size of resected liver metastases varies between 4.5 cm and 5 cm. 5,10,14,15 In addition, Sal et al reported that 41% of the resections included liver metastases of >10 cm in diameter. 15 No differences have been demonstrated between the size of liver lesions according to their origin (parenchymal or peritoneal).…”
Section: Discussionmentioning
confidence: 99%
“…5,10,14,15 In addition, Sal et al reported that 41% of the resections included liver metastases of >10 cm in diameter. 15 No differences have been demonstrated between the size of liver lesions according to their origin (parenchymal or peritoneal). 1 The current authors found no significant difference between the mean sizes of liver metastases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the fact that the normal appearance of gastro intestinal system and pancreas, increased levels of CA 19.9 (1782.7 U/mL) is remarkable in our case and appropriate with isolated ovarian metastasis. Besides it has been reported that elevated levels of CA 19.9 is correlated with poor prognosis and advanced stage disease ( 6 ) . The metastasis rate from the biliary tumors to the ovaries is very low in the current literature ( 1 ) .…”
Section: Discussionmentioning
confidence: 99%